2012
DOI: 10.2478/s11535-012-0064-x
|View full text |Cite
|
Sign up to set email alerts
|

Plant tissue cultures from four Tuscan globe artichoke cultivars

Abstract: The aim of the study was to examine the possibility of propagating in vitro four of the most common cultivars in Tuscany (central Italy): Terom, Violetto di Toscana, Chiusure and Empolese. The first three belong to the “Violetti” group, while cv Empolese belongs to the “Romaneschi” group. Explants were cultured on an induction medium (IM), which is a modified MS medium consisting of nitrate concentrations reduced by one quarter, 0.8 mg L−1 6-benzylaminopurine (BA) and 0.2 mg L−1 3-indole butyric acid (IBA). Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 24 publications
(44 reference statements)
1
13
0
2
Order By: Relevance
“…Because the root induction in vitro in artichoke is the critical stage, several investigations have been conducted on different cultivars and different growth regulators, such as indoleacetic acid (IAA), naphthaleneacetic acid (NAA), gibberellin (GA 3 ) in combination with/without activated charcoal (AC) [1][2][3][4][5][6]. According to previous researches, the success in root induction stage depends on genotype [7][8][9], and genotype specific protocols should be determined. López-Pérez and Martínez [9] reported that the in vitro rooting was still the main subject to investigate especially in early artichoke cultivars mainly grown the Mediterranean region.…”
mentioning
confidence: 99%
“…Because the root induction in vitro in artichoke is the critical stage, several investigations have been conducted on different cultivars and different growth regulators, such as indoleacetic acid (IAA), naphthaleneacetic acid (NAA), gibberellin (GA 3 ) in combination with/without activated charcoal (AC) [1][2][3][4][5][6]. According to previous researches, the success in root induction stage depends on genotype [7][8][9], and genotype specific protocols should be determined. López-Pérez and Martínez [9] reported that the in vitro rooting was still the main subject to investigate especially in early artichoke cultivars mainly grown the Mediterranean region.…”
mentioning
confidence: 99%
“…In this respect, Ancora et al (1981) and Morone-Fortunato et al (2005) developed in vitro techniques for micropropgation and short term conservation of Romanesco globe artichoke. Bedini et al (2012) optimized in vitro cultures of four Tuscan globe artichoke cultivars i.e., Terom, Violetto di Toscana, Chiusure and Empolese. Moreover, in vitro med-term storage of globe artichoke cv.…”
Section: Conservation Of Globe Artichoke Genetic Resourcesmentioning
confidence: 99%
“…In the initiation stage, Olivera (2000) managed to regenerate thornless artichoke microplants of 3-4 cm height with 4-5 leaves after 10 weeks from meristems introduced in vitro in the MS medium supplemented with BAP 0.2 ppm and ANA 0.5 ppm. Bedini, Lucchesini, Bertozzi and Graifenberg (2012) in his study used an induction medium containing MS medium (Murashige & Skoog, 1962) with concentrations of ¼ KNO 3 and ¼ NH 4 NO 3 added with BA 0.8 mg l −1 and IBA 0.2 mg l −1 for the initiation stage; initially, the containers were placed in darkness and then in the light for 3 weeks.…”
Section: Introductionmentioning
confidence: 99%
“…Elia, Conversa, Montervino, and Lotti (2007) obtained better multiplication results using the MS medium (Murashige & Skoog, 1962) supplemented with AIA 5.4 μM + 2iP 4.9 μM + KIN 2.3 μM + BAP 0.4 μM with a cytokinin/auxin ratio of 1: 4-obtained 4.5 shoots/explant with an average shoot length of 41.9 mm. In a study by Bedini et al (2012), the same culture medium was used as in the initial phase by modifying the content of plant regulators adding BAP 0.03 mg l −1 and GA3 0.05 mg l −1 in 25 ml containers during the first three subcultures obtaining 4.4 shoots per explant in the cv. Empolese.…”
Section: Introductionmentioning
confidence: 99%